STRATEGI PENCEGAHAN KRIMINALITAS BERBASIS KOMUNITAS DI KECAMATAN PASMAH AIR KERUH KABUPATEN EMPAT LAWANG PROVINSI SUMATRA SELATAN - Purnawan, Heru; Agung, Jumrotul; Noviyanto, Hernowo (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
This study aims to analyze the effectiveness of community-based crime prevention strategies in reducing crime rates in Pasmah Air Keruh Sub-district, Empat Lawang Regency, South Sumatra Province. The research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The findings indicate that community-based crime prevention programs have significantly contributed to a decrease in crime over the past four years. Contributing factors to criminal activity include alcohol consumption, drug abuse, unemployment, low educational attainment, economic hardship, and the social environment. Implemented programs include the Community Early Awareness Forum (FKDM), community policing, village security posts by Satpol PP, public outreach, and routine joint patrols. Major obstacles identified are low community participation, limited awareness of crime risk factors, and inadequate security infrastructure. Community education and training initiatives need to be strengthened to increase public awareness and foster active participation in sustainable crime prevention efforts.